Tinjauan Singkat Terhadap Tindak Pidana Korupsi dan Dampaknya Terhadap Masyarakat - Dharyanto, Ikang (Pelita Harapan University, 2006)
Corruption in Indonesia has become widely in the society. The existence through the years can be seen from the corruption cases that always occur and have resulted the big losses of the economic demand. Besides that, we can also see from the quality of the criminal act which is done with great and neat systems and also has come into the social life in a country. Â The raise of the corruption can bring a big destruction to the economic life in Indonesia. Â The corruption s act showed a government failure to achieve the aim that been made in the constitution that to make prosperous to the Indonesian society. Â Corruption can make a complicated matter, such as make the investor runaway from Indonesia and don t want to put the money in Indonesia. If the government never aware about this condition so it can make negatives impacts, such as all legal rules been neglected by all people, the people never believed anymore to the government, and the bad thing was the paralyzed to the economic and politic development in Indonesia.